Freedom of Expression in the Spread of Hoax News on Social Media Between Indonesia and South Korea - Rini Jarwati Indah N. C; Dhea Zeftyaningrum; Richo Febria Putra; Dio Ashar Wicaksana (CV. Pustaka Parawali, 2024)
Freedom of expression is the right of people to freely express their opinions through various media without considering their limitations and without violating the rights of others. One example of the spread of fake news that has the potential to damage reputation is the spread of hoax news, which mainly occurs in Indonesia and South Korea. This study aims to understand the comparison of regulations governing the spread of fake news in Indonesia and South Korea and how the government faces this problem in the election process. The method used is a normative methodology through a legislative approach, which allows a comparison of freedom of opinion regulations in spreading fake news between Indonesia and South Korea. In Indonesia, freedom of opinion is regulated in Article 28 E paragraph (3) of the 1945 Constitution of the Republic of Indonesia and Article 1 paragraph (1) of Law Number 9 of 1998 concerning Independence, while South Korea indirectly regulates freedom of opinion regulated in Article 21 paragraph 4 of the South Korean Law. In Indonesia and South Korea, special regulations are given regarding sanctions against perpetrators of spreading fake news, in Indonesia is contained in Article 28, paragraph (1) and paragraph (2) of Law Number 11 of 2008 concerning Information and Electronic Transactions, while South Korea is substantially stated in Criminal Act No. 14415 Article 307. However, it is necessary to ensure that freedom of expression is not used to circulate fake news, which is a symptom of a problem rather than the root of the issue itself.